Gain Enchancement of Microstrip Leaky-Wave 1x3 Antenna with V-Slot - MUHAMAD WAHYU IQBAL; VINA OKTAVIANI; BASO MARUDDANI (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2025)
This study aims to improve the performance of a microstrip leaky-wave antenna by adding a 1x3 array configuration and a V-slot structure for WLAN applications in the 5.925 − 6.425 GHz, using an FR-4 substrate with a dielectric constant of 4.6. Simulations were conducted to evaluate the parameters of S11, VSWR, bandwidth, and gain. The use of an array and V-slot aims to enhance both gain and bandwidth. Simulation results show the array and V-slot configuration achieved a bandwidth of 570 MHz (5.86 − 6.43 GHz) and gain of 7.02 dBi at 6 GHz. Compared to the microstrip leaky-wave antenna without a V-slot, the proposed configuration improved the bandwidth by 270 MHz (90%) and the gain by 0.82 dBi (13.3%). These results indicate that the addition of an array and V-slot structure effectively enhances antenna performance for wireless communication applications.